1998
DOI: 10.1073/pnas.95.6.3020
|View full text |Cite
|
Sign up to set email alerts
|

Bridging of β-catenin and glycogen synthase kinase-3β by Axin and inhibition of β-catenin-mediated transcription

Abstract: Axin antagonizes the developmental effects of Wnt in vertebrates. We show here that Axin simultaneously binds two components of the Wnt pathway, ␤-catenin and its negative regulator glycogen synthase kinase-3␤. In mammalian cells, Axin inhibits Wnt-1 stimulation of ␤-catenin͞ lymphoid enhancer factor 1-dependent transcription. Axin also blocks ␤-catenin-mediated transcription in colon cancer cells that have a mutation in the adenomatous polyposis coli gene. These findings suggest that Axin, by forming a comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
199
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(204 citation statements)
references
References 23 publications
5
199
0
Order By: Relevance
“…We and others have demonstrated that Wnt-1 or Dvl1, when expressed in NIH3T3 cells, can activate the transcription regulator 16,28,29). This activation depends on β-catenin and is suppressed by GSK-3β and axin.…”
Section: Dep Domain Interacts With Upstream Regulators Of Dvlmentioning
confidence: 79%
“…We and others have demonstrated that Wnt-1 or Dvl1, when expressed in NIH3T3 cells, can activate the transcription regulator 16,28,29). This activation depends on β-catenin and is suppressed by GSK-3β and axin.…”
Section: Dep Domain Interacts With Upstream Regulators Of Dvlmentioning
confidence: 79%
“…A study of hepatocellular carcinomas showed that Axin mutations lead to inappropriate b-catenin-mediated transcription (Satoh et al 2000). Overexpression of Axin in colon cancer cells can rescue the accumulation of b-catenin that results from APC mutation (Behrens et al 1998;Hart et al 1998;Kishida et al 1998;Sakanaka et al 1998).…”
Section: Axin the Central Phosphorylation Scaffoldmentioning
confidence: 99%
“…Overexpressed Axin destabilizes β-catenin (Behrens et al, 1998;Hart et al, 1998;Ikeda et al,1998;Kishida et al, 1998;Nakamura et al, 1998;Sakanaka et al, 1998;Yamamoto et al, 1998). Loss of Axin results in nuclear accumulation of β-catenin followed by formation of the β-catenin-TCF transcriptional complex involving transcriptional activation of its target genes (Sakanaka et al, 1998). Mutations of Axin have been reported in hepatocellular carcinoma (Clevers, 2000;Satoh et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Axin is a multi-domain scaffold protein that associates directly with β-catenin, GSK3β, and phosphatase PP2A (Hsu et al, 1999). Axin is implicated in down-regulation of Wnt/β-catenin signaling Itoh et al, 1998;Sakanaka et al, 1998;Kikuchi et al, 2006). There are two vertebrate Axins (Axin 1 and Axin 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation